Natural-Killer-Derived Extracellular Vesicles: Immune Sensors and Interactors - Federici, Cristina; Shahaj, Eriomina; Cecchetti, Serena; Camerini, Serena; Casella, Marialuisa; Iessi, Elisabetta; Camisaschi, Chiara; Paolino, Giovanni; Calvieri, Stefano; Ferro, Simona; Cova, Agata; Squarcina, Paola; et al. (Frontiers in Immunology, 2020)
Natural killer (NK) cells contribute to immunosurveillance and first-line defense in the control of tumor growth and metastasis diffusion. NK cell-derived extracellular vesicles (NKEVs) are constitutively secreted, are biologically active, reflect the protein and genetic repertoire of their originating cells and exert anti-tumor activity in vitro and in vivo. Cancer can compromise NK cell functions, a status potentially reflected by their EVs. Hence, NKEVs could on the one hand contribute to improve cancer therapy by interacting with tumor and/or immune cells and on the other hand sense the actual NK cell status in cancer patients. Here we investigated the composition of healthy donors’ NKEVs, including NK-microvesicles and exosomes, and their interaction with uncompromised cells of the immune system. To sense the systemic NK cell status in cancer patients we developed an immune enzymatic test (NKExoELISA) that measures plasma NK cell-derived exosomes, captured as tsg101+CD56+ nanovesicles. NKEV mass spectrometry and cytokine analysis showed the expression of NK cell markers i.e NKG2D and CD94, perforin, granzymes, CD40L and other molecules involved in cytotoxicity, homing, cell adhesion and immune activation, together with EV markers tsg101, CD81, CD63 and CD9 in both, NK-derived exosomes and microvesicles. Data are available via Proteome Xchange with identifier PXD014894. Immunomodulation studies revealed that NKEVs displayed main stimulatory functions in PBMCs, inducing the expression of HLA-DR and co-stimulatory molecules on monocytes and CD25 expression on T cells, which was maintained in the presence of LPS and IL-10/TGFβ, respectively. Furthermore, NKEVs increased the CD56+ NK cell fraction, suggesting that effects mediated by NKEVs might be potentially exploited in support of cancer therapy. The measurement of circulating NK exosomes in plasma of melanoma patients and healthy donors evidenced lower levels of tsg101+CD56+ exosomes in patients with respect to donors. Likewise, we detected lower frequencies of NK cells in PBMCs of these patients. This data highlights the potential of NKExoELISA to sense alterations of the NK cell immune status.